In Vivo Applications of CRISPR-Based Genome Editing in the Retina - Yu, Wenhan; Wu, Zhijian (Frontiers in Cell and Developmental Biology, 2018)
The rapidly evolving CRISPR-based genome editing technology is bringing revolutionary changes to the entirety of the life sciences. In this mini-review, we summarize the recent progress of in vivo applications of CRISPR genome editing in retinal studies. Non-viral and viral vector mediated delivery have been developed for temporary or persistent expression of CRISPR components in retinal cells. Although in theory CRISPR-based genome editing can correct a large number of mutant genes responsible for a variety of inherited retinal disorders (IRDs), precise gene modification relies on homology-directed repair (HDR) – the efficiency of which is not currently high enough for meaningful benefit. Development of CRISPR-based treatment for retinal diseases thus far has been mainly focused on gene knock-out or gene deletion in which the highly efficient non-homologous end joining (NHEJ) repair pathway is involved. Therapeutic benefits have been achieved in a few rodent models of retinal diseases following CRISPR treatment. The in vivo applications of CRISPR have also facilitated studies of gene function in the retina. As off-target events and immune responses are still the major concerns, continuous development of safer CRISPR genome editing system is prerequisite for its clinical applications.